2016
DOI: 10.18488/journal.8/2016.4.1/8.1.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Economic Growth Nexus in BRICS: Evidence from ARDL Bound Testing Approach

Abstract: The present study investigated the inflation growth nexus in the context of BRICS countries. The study used time series data covering from the period 1980 to 2012. The data sources are cumulated from the World Bank, World Economic Outlook (WEO). The empirical findings of the study indicate that a long run positive relationship between inflation and economic growth only for China and South Africa at the 5 percent level of significance. The study also found that there is a unidirectional causality between econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…(2013) establish a 17 percent threshold; Mahawiya (2015) find a 17.9 percent for ECOWAS countries (including Ghana) and 14.5 percent for SADC countries (including South Africa); Ibarra and Trupkin (2016) find a 19.1 percent inflation threshold whilst Ndoricimpa (2017) estimate a 6.7 percent inflation threshold Under the second group of studies, those being panel studies which only include South Africa in the empirical analysis, the available studies can be narrowed down to the works of Seleteng et al (2013), Bittencourt et al (2015), Behera and Mishra (2016) and Manamperi (2014). Note that whilst the works of Manamperi 2014, Bittencourt et al (2015) and Behera and Mishra (2016) all assume linear empirical frameworks, on the other hand, the study of Seleteng et al (2013) applies a nonlinear empirical framework (smooth transition regression model). In particular, Manamperi (2014) find a negative inflation-growth relationship in the short-run and no significant relationship over the long-run; Bittencourt et al (2015) establish a long-run negative inflation-growth relationship; Behera and Mishra (2016) find a positive relationship for South Africa in the short-run which turns positive in the long-run whereas Seleteng et al (2013) estimate an inflation threshold of 18.9 percent.…”
Section: Empirical Review Of Associated Literaturementioning
confidence: 99%
“…(2013) establish a 17 percent threshold; Mahawiya (2015) find a 17.9 percent for ECOWAS countries (including Ghana) and 14.5 percent for SADC countries (including South Africa); Ibarra and Trupkin (2016) find a 19.1 percent inflation threshold whilst Ndoricimpa (2017) estimate a 6.7 percent inflation threshold Under the second group of studies, those being panel studies which only include South Africa in the empirical analysis, the available studies can be narrowed down to the works of Seleteng et al (2013), Bittencourt et al (2015), Behera and Mishra (2016) and Manamperi (2014). Note that whilst the works of Manamperi 2014, Bittencourt et al (2015) and Behera and Mishra (2016) all assume linear empirical frameworks, on the other hand, the study of Seleteng et al (2013) applies a nonlinear empirical framework (smooth transition regression model). In particular, Manamperi (2014) find a negative inflation-growth relationship in the short-run and no significant relationship over the long-run; Bittencourt et al (2015) establish a long-run negative inflation-growth relationship; Behera and Mishra (2016) find a positive relationship for South Africa in the short-run which turns positive in the long-run whereas Seleteng et al (2013) estimate an inflation threshold of 18.9 percent.…”
Section: Empirical Review Of Associated Literaturementioning
confidence: 99%
“…By using the cointegration method, the empirical result found that there is a long-run relationship between inflation and economic growth. Behera and Mishra (2016) studied the inflation growth nexus in the context of BRICS countries. By employing the ARDL model econometric technique, the study found that there is a unidirectional causality from inflation to economic growth in the context of India and bidirectional causality in the case of China.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The result also reveals that there is a unidirectional causality between CPI and GDP in the context of all South Asian countries. Behera and Mishra (2016) examined the inflation growth nexus in BRICS.…”
Section: Quarterly Journal Of Econometrics Researchmentioning
confidence: 99%